2021
DOI: 10.1186/s13018-021-02636-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative characteristics and intraoperative factors do not correlate with accomplishments of active straight-leg raising, standing up, and walking after primary total knee arthroplasty

Abstract: Background The correlations between patient characteristics and early postoperative functional performances after total knee arthroplasty have not been adequately studied. The purpose of this study was to clarify the effects of preoperative characteristics (sex, age, body mass index, American Society of Anesthesiologists grade, hospital for special surgery score) and intraoperative factors (duration of surgery and tourniquet use) on the time required to accomplish active straight-leg-raising, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Patients with hypertension and diabetes must receive blood pressure and glucose control before operation, and can drink some water to improve circulation stability and reduce postoperative insulin resistance, thus accelerating the recovery of gastrointestinal function [ 20 ]. Ishii Yoshinori et al showed that insulin resistance could be reduced if patients undergoing TKR were to eat and drink water moderately before surgery, and their hospital stay could be shortened to (8.54 ± 0.54) d [ 21 ], which was consistent with the results obtained herein. Not only that, the combination of preoperative analgesia and postoperative multi-mode analgesia can enhance the analgesic effect and alleviate central sensitization in patients.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with hypertension and diabetes must receive blood pressure and glucose control before operation, and can drink some water to improve circulation stability and reduce postoperative insulin resistance, thus accelerating the recovery of gastrointestinal function [ 20 ]. Ishii Yoshinori et al showed that insulin resistance could be reduced if patients undergoing TKR were to eat and drink water moderately before surgery, and their hospital stay could be shortened to (8.54 ± 0.54) d [ 21 ], which was consistent with the results obtained herein. Not only that, the combination of preoperative analgesia and postoperative multi-mode analgesia can enhance the analgesic effect and alleviate central sensitization in patients.…”
Section: Discussionsupporting
confidence: 89%
“…Pre-operatively, these defects commonly present themselves and amplify the limitation of knee motion during the surgical procedure and subsequent hospitalization [ 50 ]. Skeletal muscle health plays a crucial role in the success of postoperative treatment [ 51 ]. Moreover, when painful stimuli are present and isometric muscle contractions are performed, pain processing is suppressed, and analgesic effects are elicited by working memory tasks [ 52 ].…”
Section: Discussionmentioning
confidence: 99%